CONSTRUCTIVE-SYNTHESIZING MODELING OF NATURAL LANGUAGE TEXTS (Computer systems and information technologies, 2023)
Means for solving the problem of establishing the natural language texts authorship were developed. Theoretical tools consist of a constructors set was developed on the basis of structural and production modeling. These constructors are presented in this work. Some results of experimental studies based on this approach have been published in previous works by the author, the main results should be published in the next ones.Constructors developed: converter of natural language text into tagged, tagged text into a formal stochastic grammar and the authors style similarity degree establishment of two natural language works based on the coincidence of the corresponding stochastic grammars (their substitution rules).The proposed approach makes it possible to highlight the semantic features of the author's phrases construction, which is a characteristic of his speech. Working with a sentence as a unit of text to analyze its construction will allow you to more accurately determine the author's style in terms of the use of words, their sequences and characteristic language constructions. Allows not to be attached to specific parts of speech, but reveals the general logic of building phrases.
Keywords: natural language texts; constructive-synthesizing modeling; establishing authorship; formal grammars; stochastic grammars; text models